A pox on fools : the true believers, grifters, and cynics who convinced us to reject vaccines - Levenson, Thomas (Random House, 2026)
"Since the advent of smallpox inoculation in the eighteenth century, the idea that a disease introduced to the body in some lesser, weakened form might prevent full-blown infection has been one of the greatest public health insights of the modern era, inspiring the invention of numerous vaccines and saving countless human lives. But, just as humanity acquired the god-like power to stop infectious disease in its tracks, some feared we had gone too far, leading to the skepticism that has hijacked public health discourse today.In three sweeping essays written for our current moment of scientific mistrust, Thomas Levenson searches for the origins of the most common arguments against vaccines: that they are unnatural; that they are more dangerous than the illnesses they claim to prevent; and that they are an affront to freedom. Each arose from the earliest development of particular vaccines and the campaigns to distribute them. Even as the pattern repeats, Levenson reveals how innocent that skepticism initially was and, in each case, how very human fears and questions ultimately turned into something darker, where no truth would be enough to overcome the doubt. Searing but ultimately empathetic, A Pox on Fools explores the human impulse to question and wonder--sometimes past the point at which the very act of questioning turns deadly."--